Acceptance of health messages conveyed by parasocial opinion leaders on twitter among followers - Chew, Saw Teck; Emma Mohamad,; Sabariah Mohamed Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Social media does not only provide a space for individuals to communicate, but it also encourages individuals to find and share health information. This situation has led to a change in the patterns and functions of health opinion leaders that exist on social media. Health opinion leaders influence media users by sharing and delivering health information and are capable of fostering parasocial relationships with media users. Therefore, it is essential to investigate the process by which parasocial opinion leaders shape health messages on social media. In correspondence, this study sought to understand the level of acceptance of health messages among Twitter users of the information tweeted by parasocial opinion leaders. In-depth interviews were conducted on 25 followers of parasocial health opinion leaders on Twitter. This study found that the formation of health messages and information conveyed by parasocial health opinion leaders could influence their followers. Four forms of message reception were identified in this study: 1) information and complexity reduction (a description, information delivery style, information sharing, information, and health literacy, and correction of information and mythical perceptions), 2) health orientation, 3) stimulation of interest, and 4) strengthening of the image and ethics of professionalism. Additionally, this study also discovered that media users perceived health opinion leaders as mentors, family members, friends, and idols.